No evidence of a demographic response to experimental herbicide treatments by the White-crowned Sparrow, an early successional forest songbird. (4th April 2019) - Rivers, James W; Verschuyl, Jake; Schwarz, Carl J; Kroll, Andrew J; Betts, Matthew G
Abstract: Early-successional forest birds, which depend on disturbance events within forested landscapes, have received increased conservation concern because of long-term population declines. Herbicides are often used to control vegetation within early-successional forests, with unknown effects on avian vital rates. We used a large-scale experiment to test how nest and post-fledging survival were influenced by herbicide intensity within managed conifer plantations across 2 breeding seasons. We created a gradient of 4 stand-scale herbicide treatments (light, moderate, and intensive, and no-spray control) and evaluated the reproductive response of the White-crowned Sparrow ( Zonotrichia leucophrys ), a declining songbird in managed forest landscapes of the Pacific Northwest. Against initial predictions, we found no evidence that either daily nest survival ( n > 760 nests across all treatments) or post-fledging survival ( n = 70 individuals reared in control and moderate treatments) were influenced by herbicide application intensity. Increased herbicide intensity resulted in an extensive reduction in vegetation cover at both stand and nest-patch scales; in contrast, vegetative cover at nest sites did not differ across herbicide treatments, nor was nest survival related to vegetation concealment measures. As the largest experimental investigation to assess forest herbicide effects on songbird demography, our study indicates that components of sparrow reproductive success were not influenced by experimental vegetation control measures, although additional work on other early-successional species will be useful to evaluate the generalities of our findings.